Endodontic management of permanent mandibular first molar with middle mesial canal: A case report - Hadi Rajeh Alfahadi; Fawaz Hamad Alkazman; Ahmed Bamanie; Mesfer Saleh Alwadai (Wolters Kluwer Medknow Publications, 2021)
Endodontic treatment of a permanent mandibular first molar is often difficult due to its related complex variations. The root cause of endodontic failure is the inability of a practitioner to recognize and manage an irregular root canal system. Knowledge of dental anatomy, thorough examination, and utilization of recent diagnostic tools are required for an effective root canal treatment. A 31-year-old Saudi male patient presented to the endodontic clinic for endodontic treatment of the mandibular left first molar (#36). Clinical examination using a dental operating microscope (DOM) followed by radiographic examination including cone-beam computed tomography (CBCT) revealed the diagnosis of asymptomatic apical periodontitis in a previously attempted root canal therapy which was incomplete. The periapical disease involved middle mesial canal (MMC) intermingling with the mesiobuccal (MB) in the mesial root. The root canal treatment was successfully carried out with no symptoms during 6 months of follow-up period. This case reports the presence of unusual presentation of MMC and MB canal in the mandibular first molar, which had resulted in postendodontic complications, which was diagnosed using CBCT and successfully managed with good prognosis. Dentists can use technical and imaging advancements including the DOM and CBCT to recognize anatomical variations in the root canal system, especially in cases of postendodontic failures or complications.